Enhancing Vanadium Redox Battery Performance Using Tungsten-Bismuth-Based Oxide Nanostructures as Electrode Modifiers - Al Najjar, Taher (AUC Knowledge Fountain, 2022)
Renewable energy power plants require high efficiency conversion and storage systems that can store high amounts of energy and can be integrated with the electrical grid. Vanadium redox flow batteries are very promising for this application. However, one major drawback of VRFBs is their low power density which means that right now they cannot replace non-renewable energy sources. Different carbon materials are used as electrodes in VRFBs and each carbon material affects the battery’s performance in a different way. Modification of these electrodes can increase the power density of the battery. Some metal oxides like tungsten oxide can enhance vanadium reactions. Other metal oxides like bismuth are known to inhabit the partistic reactions that degregate the electrode stucture and lower the battery overall performance. The aim of this thesis is to study the effect of using mixed metal oxides with different molar ratios and structures on the performance of carbon cloth electrodes for the negative vanadium redox reaction V2+/V3+. Results showed that modifying the electrode with the two metal oxides gave obvious enhancement effect on the kinetics of the V2+/V3+ reaction and that that the enhancement was directly related to structure of the metal oxides and the composition of the metal oxide in use. The best result for the tungsten oxide modified carbon cloth electrodes was demonstrated by the tungsten oxide nanowires. For the mixed metal oxide, tungsten bismuth oxide with molar ratio of W:Bi = 2:1 gave the best results with the lowest peak separation and highest peak current. All the modified electrodes had lower charge transfer resistance than the pristine carbon cloth electrodes which translate into better electrode performance.